Extending structural subsumption reasoning algorithms for ontology matching - Jian-xin LIAO; Xiu-lei LIU; Xiao-min ZHU; Hai-feng SUN; Jing-yu WANG (Tongxin xuebao)
For exploiting semantics implied in constructors and axioms in an ontology,a structural subsumption reasoning algorithm was extended to match ontologies.The implied semantics was first enabled to be read-off easily by rephrasing entities in an ontology into normal forms; then the syntactical structure of the normal forms were compared to infer correspondences between entities,one from each ontology.The prototype was evaluated over four in use ontologies and compared against twelve methods.The experiments show that its performance is higher than other solutions on average.